The javelin. Basic javelin aerodynamics and flight characteristics - Maheras, A. V. (Techniques Magazine, 2013)
This is the first part of a two part article regarding javelin aerodynamics. It deals with center of mass (CM), center of pressure (CP), pitching moment (PM), lift, drag and l-d ratio, center of pressure and behavior of javelin in flight, angle of attack and the attack angle in head and tail wind, wind effects in javelin throwing.